Evaluation For Learning Development During The Covid-19 Pandemic in Pasangkayu - Juraid Abdul Latief; Darsikin; Haeruddin; Abdul Rahman (Kirana Publisher (KNPub), 2023)
This research aims to analyse the evaluation for learning development during the Covid-19 Pandemic in Pasangkayu. The dynamics of learning in schools during a pandemic needs to be described so that the right program can be designed. Given the many problems found in the field, it is very important to examine the learning process that occurred during the Covid-19 pandemic in Pasangkayu. The results of the study show that the application that is widely used by teachers in the Pasangkayu is WhatsApp. Most teachers do not use online learning applications. This shows that teachers in the Pasangkayu do not have the skills to use digital applications in learning. However, some teachers have used Google for Education, teacher rooms and learning houses as a means of interacting with students online. The recommendations that can be used as alternative policies are make sure students return to school with communicating with parents and the community, complete proper school infrastructure, place a strong emphasis on learning recovery, restore student learning discipline, supporting the independent curriculum, provide training on the use of learning technology to teachers, development of interests and talents in the form of art, holding competitions between districts/schools such as competitions, expand access to distance learning by expanding internet connections, encourage schools to participate in the driving school program, involve parents in school development, ensure that these low-income students receive additional support, cooperate with the private sector, and conducting a technology skilled installation and literacy movement campaign.